Subacute Sclerosing Panencephalitis Outcomes Based on the Treatment Initiation Stage: A Systematic Literature Review - Gabija Gurskaitė; Rūta Samaitienė Aleknienė (Neurologijos seminarai, 2024)
Background and Objectives: Subacute Sclerosing Panencephalitis (SSPE) is a rare, progressive, and fatal neurological disorder caused by persistent measles virus infection, predominantly affecting children. The recent resurgence of measles globally, driven by declining vaccination rates, has highlighted the need for effective SSPE management strategies. Currently, treatment approaches focus on managing symptoms and slowing down the disease progression. This review aims to systematically evaluate treatment outcomes for SSPE based on the disease stage at which the therapy is initiated. Materials and Methods: A comprehensive PubMed search identified publications from 1994 to 2024 with the objective to list studies covering in detail SSPE treatment regimens and reporting on patient outcomes by the disease stage at treatment initiation. The inclusion criteria were as follows: randomized controlled trials, cohort studies, and case reports which clearly documented the treatment initiation stages and outcomes. The review classified cases into six treatment groups based on the most used medication combinations for the early (stages I–II) and advanced stages (stages III–IV) of SSPE. Results: A total of 30 studies comprising 80 SSPE cases met the inclusion criteria. Ribavirin combined with interferon and Isoprinosine showed favorable outcomes, particularly in early-stage patients. In contrast, Isoprinosine monotherapy resulted in the highest progression rates across both stages. Other combinations demonstrated varied effectiveness. Antiepileptic drugs provided symptomatic relief but did not alter the disease progression. Conclusions: This systematic review highlights the influence of the SSPE treatment initiation stage on the patient outcomes, suggesting that a tailored approach based on the disease progression may improve the treatment efficacy.